Correlation of PSA Level and ISUP Grade Group with Scintigraphic Bone Metastases Detection in 36 Prostate Cancer Patients - SOSSA, JEAN; FANOU, LIONELLE; Houngnigbe, Adanvo Isaac; Hounto, Yao Félicien; YEVI, DODJI MAGLOIRE INÈS; Hodonou, Fred Jean-Martin; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES (My University, 2023)
Background: We need population-specific clinical features that can predict bone metastases as an affordable therapeutic decision-making tool in newly diagnosed prostate cancer patients as scintigraphy or positron emission tomography are not available and as no such study had ever been performed in our country. Objective: To determine biologic and pathologic criteria that can predict the scintigraphic detection of bone metastases in our prostate cancer patients. Patients and Method: We analyzed with student’s t test and logistic regression the PSA level, the ISUP grade and the scintigraphic data retrospectively collected in newly diagnosed prostate cancer patients. Results: In ten years, 36 prostate cancer patients were sent to the Korle Bu Teaching Hospital in Accra (Ghana) for bone scintigraphy (mean age = 63.9 years; 55.6%, 19.4% and 25.0% ISUP grade ≤ 2, 3 or ≥4). Among 28 patients who had performed the bone scintigraphy, 6 (21.4%) presented bone metastases, 22 (78.6%) had no bone metastasis. The mean PSA level was 36.7ng/mL in the non-metastatic patients and 97.7 ng/mL in the metastatic patients. The difference in PSA level between the 2 groups was significative (p = 0.041). 63.6% of the non-metastatic cancers versus 16.7% of the metastatic cancers were ISUP grade 2 or less. Inversely, 36.4% of the non-metastatic cancers versus 83.3% of the metastatic cancers were ISUP grade 3 or more. The difference was significative in the ISUP grade 2 or less (p = 0.035), was significative in the ISUP grade group 3 or more (p = 0.035). Metastasis was more likely in prostate cancer patients with PSA equal 30 ng/mL or more and ISUP grade 3 or more (83.3%) than in prostate cancer patients with PSA less than 30 ng/mL and ISUP grade less than 3 (16.7%) [OR = 13.7; CI 95% (1.59; 31.0); p = 0.035]. Conclusion: The scintigraphic detection of bone metastases is low in patients
Keywords: Metastasis; Prostate Cancer; Bone Scintigraphy